Why Hospitals Fail : Between Theory and Practice - Godbole, Prasad; Burke, Derek; Aylott, Jill (Springer International Publishing : Imprint: Springer, 2017)
This book explores the current wider political, social and economic context of hospitals in the public and private sector globally and identifies the push and pull tension between the demands of the quality regulator and the requirements of health care commissioning processes. This book draws on the evidence of what works to improve the quality of hospital services in the development of medical and clinical leadership models. The book seeks to develop a specific paradigm shift in understanding the development of medical leaders by promoting a culture of engagement through participation and one that is defined by the experiences of medical leaders. The editors examine new and emergent models of leadership and their contribution to explain effective and sustainable change and suggest that theoretical models of leadership are often unable to explain many of the practice led challenges presented in hospitals. It will be useful reading for specialists seeking to develop their own learning as a leader and who identify their learning needs.
Keywords: Medicine.; Health administration.; Practice of medicine.; elektronické knihy; electronic books